Adopt best practices to meet unique needs of adult learners. Issue 6 (1st August 2022) - Sutton, Halley
Abstract : "My interest in adult learners really comes from my own experience, " said Susan J. Barcinas, Ph.D., Associate Professor and Coordinator for the Adult, Workforce, and Continuing Professional Education Program in the Department of Educational Leadership, Policy, and Human Development at North Carolina State University.